The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2147/opth.s36331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trabeculectomy on retrobulbar circulation and visual field progression in patients with primary open-angle glaucoma

Abstract: BackgroundThe purpose of this study was to investigate the relationship between retrobulbar circulation and visual field change in eyes with primary open-angle glaucoma following unilateral trabeculectomy.MethodsTwenty-one patients with primary open-angle glaucoma were prospectively enrolled. Retrobulbar circulation was evaluated using color Doppler imaging. The peak systolic velocity, end-diastolic velocity, and resistive index were evaluated in the central retinal artery, temporal site of the short posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(14 reference statements)
1
6
0
Order By: Relevance
“…In our study, OPP significantly increased after trabeculectomy. These results were similar to those of the studies by Yamazaki et al 17 and Berisha et al, 5 both of whom found a significant increase after trabeculectomy. Also, many previous studies measured SFCT with EDI-OCT and they found that it was significantly associated with OPP.…”
Section: Eyesupporting
confidence: 92%
“…In our study, OPP significantly increased after trabeculectomy. These results were similar to those of the studies by Yamazaki et al 17 and Berisha et al, 5 both of whom found a significant increase after trabeculectomy. Also, many previous studies measured SFCT with EDI-OCT and they found that it was significantly associated with OPP.…”
Section: Eyesupporting
confidence: 92%
“…According to Kara et al, choroidal thickening is related to an OPP increase induced by IOP reduction [24]. This corresponds to the retrobulbar blood flow rising observed after trabeculectomy [37]. Nickla and Wallman presumed that the choroidal thickness increase stemmed from two mechanisms [38]: first the synthesis of osmotically active proteoglycans, which help pull water into the choroid; second, to the increase in the size or number of the choriocapillaris vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Explanation for this thickening remains uncertain. Previous studies hypothesized that the vessel size could increase due to a rise in ocular blood flow [37]. Reis et al also suggested that this modification is caused by size changes in RGC axons and astrocytes after IOP reduction [28].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few earlier studies reported on a surgery-induced MD decline. Most studies found no influence on the MD (Tavares et al 2006;Sehi et al 2010;Yamazaki & Hayamizu 2012;Balekudaru et al 2014;Wright et al 2015;Islamaj et al 2018); one study found a deterioration of the MD after a TE (Hagiwara et al 2000). In the latter study, the postoperative MD was assessed at the end of the follow-up (mean follow-up duration was 4.75 years).…”
Section: Discussionmentioning
confidence: 99%